DESIGN, IMPLEMENTATION, AND EVALUATION OF A PRACTICE-BASED DEVELOPMENT PROJECT. - Wandera, Bernard; Nalubega, Jane Frank; Akankwasa, Edith; Okello, Elizabeth; Kavuma, David (Student’s Journal of Health Research Africa, 2025)
Background. A project is being undertaken to improve the functionality and well-being of children with disabilities, particularly in Fort Portal City and Kabarole District, through improved access to quality health care, habilitation, and rehabilitation services. The initial phase of the project targeting Kabarole Hospital started in March 2021 and ended in June 2022. Project design. The project seeks to increase access of CWDs to comprehensive, friendly services and information, strengthen the capacity of health facilities to provide quality health care and rehabilitative services to CWDs, and increase community and family awareness, support, and care to CWDs. Results. By the end of the first phase (July 2021- June 2022) of actual implementation of the project notable achievements included training 18 health facility staff as CWD FPs, formation of nine community support groups, conducting 98 monthly outreaches to community support groups and nine monthly support supervision visits to the health facilities in addition to 211 home visits to families of CWDs. Training of 22 CHWs and 9 sensitization meetings have been conducted, 25 referrals for specialty care made, and 177 CWDs have been identified and recruited into health care at the lower-level health facilities. Quality of life for CWDs has improved to 60% (from a baseline), and patient satisfaction improved to 80% (from a baseline of 30%). Access to care improved by 52%. Conclusions. Improving access to quality care for CWDs and engaging the family, peers, and larger community with active participation of CWDs and their parents/caretakers enhances the well-being of CWDs. Recommendations. While services need to be built up, a lack of interventions on multiple fronts is visible. There is therefore a need for the government and partners to give higher priority to the disability issue in the child and adolescent health agendas.